REPLENISHMENT, CRYSTAL ACCUMULATION AND FLOOR AGGRADATION IN THE MEGACRYSTIC KAMERUKA SUITE, AUSTRALIA - Collins W.J.; Wiebe R.A.; Healy B.; Richards S.W. (My University, 2006)
Detailed field evidence indicates that the Kameruka Suite plutons of the Bega Batholith, eastern Australia, grew by crystal accumulation on the floor of a magma chamber. Depositional features in the plutons, including mafic enclave channels, asymmetric enclave pillows and exotic rafts, load casts and flame structures, and graded and trough cross-beds, indicate that the pluton built progressively upward. The general eastward dip of depositional features in the main pluton implies a lower western and upper eastern contact, consistent with a basal granite–migmatite contact in the west and a sharp hornfelsic sidewall contact in the east. Mafic, felsic and composite dykes, most common near and below the basal western contact, are interpreted as conduits for magma chamber replenishment and imply open-system behaviour during pluton construction. Textural relations are also consistent with an open-system, cumulate origin. Typically, centimetre-scale grains of quartz, plagioclase and megacrystic alkali feldspar form a touching framework with interstices filled with smaller biotite flakes and smaller intercumulus quartz and feldspar crystals. Alkali feldspar megacrysts vary from euhedral and unzoned, to mantled and partially replaced by plagioclase, to ovoid and completely pseudomorphed by quartz–albite aggregates. The common occurrence of mantled and pseudomorphed alkali feldspar in mafic enclaves, and in hybrid tonalitic rocks forming the matrix to enclave swarms, suggests that replacement or resorption of granitic primocrysts was associated with mafic replenishments. The occurrence of all megacryst types at outcrop scale implies extended alkali feldspar crystallization in different parts of the chamber, thorough stirring during, or after, periodic replenishment, and final settling in a cumulate mush. The bulk composition of the cumulate mush, represented by granodiorite, cannot represent the emplaced magma. Compositional variation can be modelled by variable degrees of crystal accumulation from a parental, silica-rich melt represented by the silicic dykes. As dykes periodically fed the magma chamber, crystals accumulated on the floor, and more evolved melts probably erupted from its roof. Thus, the average composition of the magma, and the cumulus minerals, may have remained relatively constant, and the sublinear chemical trends that typify the Kameruka Suite simply reflect differing proportions of melt and cumulate material. Sublinear chemical trends can also be explained by a restite model; however, the distinctive Ba, light rare earth element and Zr spikes at high silica can be explained only by a cumulate model, which also explains why the low-silica granites of the suite share the same chemical characteristics as the high-silica granites.
Keywords: crystal accumulation; magma chamber; open system; granitoids; Kameruka; Australia